2016
DOI: 10.1111/1477-9552.12193
|View full text |Cite
|
Sign up to set email alerts
|

Catching Up or Falling Behind in European Agriculture: The Case of Milk Production

Abstract: The paper explores and analyses the catching up and falling behind processes in the European dairy sector over the period 2004–2011, using a stochastic metafrontier multiple output distance function for 24 EU Member States. The metafrontier estimates reveal considerable productivity differences in milk production across the EU at the regional (NUTS‐2) level. Milk yield per cow is the highest in the old Member States, especially in those regions located in the northwest of the EU, while the lowest productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 32 publications
4
47
2
Order By: Relevance
“…Cechura et al . () investigated catching up and falling behind processes in the milk sector for 24 EU Member States over the period 2004–2011. Their metafrontier estimates revealed that there are considerable differences in the productivity of milk production across the EU: productivity is highest in the Old Member States, especially in the north west of the EU.…”
Section: Previous Studies Of Cross Country Tfp Patterns and Convergenmentioning
confidence: 99%
See 3 more Smart Citations
“…Cechura et al . () investigated catching up and falling behind processes in the milk sector for 24 EU Member States over the period 2004–2011. Their metafrontier estimates revealed that there are considerable differences in the productivity of milk production across the EU: productivity is highest in the Old Member States, especially in the north west of the EU.…”
Section: Previous Studies Of Cross Country Tfp Patterns and Convergenmentioning
confidence: 99%
“…Many studies have compared the development of agricultural productivity and efficiency in the EU over the past few decades (e.g. Ball et al ., , ; Brümmer et al ., ; Davidova et al ., ; Fogarasi and Latruffe, ; Swinnen and Vranken, ; Timmer et al ., ; Cechura et al ., ,b; Jansik et al ., ; Jansik and Irz, ). However, most of the findings reported in these studies can be used only for bilateral comparisons (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agriculture is an essential component of the European economy and society (Nazzaro and Marotta, 2016). The example of analysis of milk production in the European Union shows that the size of farms in Central and Eastern Europe is not optimal and that there are problems in the adoption of innovations and structural changes (Cechura, et al, 2016). It can be said that such a conclusion could also be relevant for Serbia.…”
Section: Introductionmentioning
confidence: 99%